Obstacle circumvention and eye coordination during walking to least and most affected side in people with Parkinson's disease - Barbieri, Fabio Augusto [UNESP]; Polastri, Paula Favaro [UNESP]; Gobbi, Lilian Teresa Bucken [UNESP]; Simieli, Lucas [UNESP]; Pereira, Vinicius Ignácio Alota [UNESP]; Baptista, André Macari [UNESP]; Moretto, Gabriel Felipe [UNESP]; Fiorelli, Carolina Menezes [UNESP]; Imaizumi, Luis Felipe Itikawa [UNESP]; Rodrigues, Sérgio Tosi [UNESP] (Elsevier, 2018)
Background: The mechanisms that contribute to gait asymmetry in people with Parkinson's disease (PD) are unclear, mainly during gait with greater environmental demand, such as when an obstacle is circumvented while walking. Objective: The aim of this study was to investigate the effects of obstacle circumvention of the least and most affected side on motor and gaze behavior in people with PD under/without the effects of dopaminergic medication. Methods: Fifteen people with PD and 15 matched-control individuals were instructed to walk along a pathway, at a self-selected velocity, and to circumvent an obstacle, avoiding contact with it. Each participant performed five trials for each side. Kinematic parameters, mediolateral and horizontal body clearance to the obstacle, strategy to circumvent the obstacle, and gaze behavior were calculated. Parameters were grouped according to the side that the obstacle was circumvented and compared by three-way ANOVAs. Results: Both people with PD and the control group presented asymmetry to circumvent an obstacle during walking, however this was exacerbated in people with PD. Individuals with PD presented safe strategies (largest mediolateral and horizontal body clearance to the obstacle, “lead-out” strategy, and higher number and time of fixations on the obstacle) during obstacle circumvention for the least affected side compared to the most affected side. In addition, positive effects of dopaminergic medication on body clearance, spatial-temporal parameters, and gaze behavior were evidenced only when the obstacle was circumvented to the least affected side. Conclusions: The obstacle circumvention to the most affected side is risky for people with PD.
Keywords: Asymmetry; Basal ganglia; Dopaminergic medication; Gait; Obstacle circumvention; Vision